Clinical Evaluation of Some Biochemical Parameters from Patients in Heamodialysis Room - Baghdad Science Journal (مجلة بغداد للعلوم)
As a marker of systemic inflammation, raised (C-reactive protein (CRP)) concentrations which are still within the normal range have been associated with an increased inflammation of chronic renal diseases (CRD). The current study aimed to establish potential determinats of raised CRP concentrations in patients who treated in Heamodialysis room,then study the relationship between CRP& some biochemical parameters related CRD We used a CRP latex reagents Kit which is based on an immunological reaction between CRP antisera bounded to the biologically inert latex particles or with CRP in the test specimens of 19 patients with (CRD) mean age 48 years ,range = 30?65 & in 21 healthy subjects as control group their age range = 30 ?45 years.